PELATIHAN KESELAMATAN KERJA PADA KARYAWAN GUDANG UD VIRGINIA TOMOHON - Firmita Dwiseli; Crifianny Praysilia Wenas; Yulianah Rahmadani (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Occupational health and safety training is a crucial strategy for preventing workplace accidents and enhancing workers’ awareness of occupational risks. This community service program aimed to improve the knowledge and understanding of warehouse workers at UD Virginia Tomohon regarding occupational safety principles, particularly in manual handling activities. The program employed a participatory approach, combining theoretical instruction with practical demonstrations. Evaluation was conducted using pre- and post-test questionnaires for 17 participants. The Wilcoxon test results indicated a significant increase in participants’ knowledge scores after the training (p = 0.008). Workers demonstrated high enthusiasm and active participation throughout the sessions. This training effectively enhanced workers’ awareness and understanding of OSH principles, fostering a culture of safety and sustainability in the workplace.